Persistence of conidia of Entomophthora muscae in relation to age, temperature, and humidity - Madeira, N. G. (Kluwer Academic Publ, 1998)
In this paper, the effect of age, humidity, and temperature on the conidial survival of Entomophthora muscae was evaluated. E. muscae was obtained from Musca domestica in a dairy in Itatiba (São Paulo, Brazil) and maintained in the laboratory by continuous passage through flies. Furthermore, the ability of conidia to infect flies at three temperatures (17, 21, and 27 degrees C), four ages of conidia (12, 72, 96, and 154 hours) and two humidities (100 and 60% RH) was evaluated. The temperature of 21 degrees C was the most favorable for the infection of house flies. Humidity was a cause of variation at 27 degrees C when the conidia were up to 12 hours old, but had no effect at lower temperatures. Conidia held at 100% RH and aged 72 hours caused no infection at 17 degrees C, but were infective at 21 degrees C. In the present study, conidia retained viability much longer than previously observed. Finally, the effect of humidity, temperature, and conidial age is discussed.
Keywords: biological control; Diptera; Entomophthoraceae; infectivity; insect pathogenic fungi; Musca domestica; Muscidae; Zygomycetes